2009
DOI: 10.1371/journal.pone.0008334
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin Signalling in the Hypothalamic Arcuate Nucleus Regulates GnRH Pulse Generator Frequency in the Rat

Abstract: BackgroundKisspeptin and its G protein-coupled receptor (GPR) 54 are essential for activation of the hypothalamo-pituitary-gonadal axis. In the rat, the kisspeptin neurons critical for gonadotropin secretion are located in the hypothalamic arcuate (ARC) and anteroventral periventricular (AVPV) nuclei. As the ARC is known to be the site of the gonadotropin-releasing hormone (GnRH) pulse generator we explored whether kisspeptin-GPR54 signalling in the ARC regulates GnRH pulses.Methodology/Principal FindingsWe ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
125
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(131 citation statements)
references
References 46 publications
1
125
2
2
Order By: Relevance
“…However, pulsatile LH release was attenuated during lactation in both the AL-fed and food-restricted dams, and this suppression of pulsatility was still observed on days 20-22 pp despite an increase in basal LH concentrations (Walker et al 1995). It has been demonstrated that the administration of a kisspeptin antagonist directly into the arcuate nucleus results in a decrease in LH pulse frequency without affecting pulse amplitude in rats, suggesting a role for arcuate nucleus kisspeptin in the regulation of LH pulse frequency (Li et al 2009). Therefore, it is tempting to speculate that low arcuate nucleus Kiss1 mRNA may contribute to the reduction in the pulsatile release of LH during lactation.…”
Section: Discussionmentioning
confidence: 95%
“…However, pulsatile LH release was attenuated during lactation in both the AL-fed and food-restricted dams, and this suppression of pulsatility was still observed on days 20-22 pp despite an increase in basal LH concentrations (Walker et al 1995). It has been demonstrated that the administration of a kisspeptin antagonist directly into the arcuate nucleus results in a decrease in LH pulse frequency without affecting pulse amplitude in rats, suggesting a role for arcuate nucleus kisspeptin in the regulation of LH pulse frequency (Li et al 2009). Therefore, it is tempting to speculate that low arcuate nucleus Kiss1 mRNA may contribute to the reduction in the pulsatile release of LH during lactation.…”
Section: Discussionmentioning
confidence: 95%
“…We analyzed the kinetics of GnRH gene transcription in association with secretion of the neurohormone in response to the secretagogue kisspeptin in hypothalamic GnRH neurons. Although inhibition of kisspeptin signaling modulates pulsatile GnRH secretion in several species (24,25), the role of kisspeptin in episodic GnRH gene expression remains elusive. We examined the effects of kisspeptin pulses on ultradian GnRH gene transcription in individual GnRH neurons and examined neuronal synchronization and secretion of the decapeptide.…”
Section: Synchronous Activation Of Gnrh Transcription and Secretion Bymentioning
confidence: 99%
“…However, continuous administration of kisspeptin abolishes gonadotropin secretion after an acute stimulatory effect, presumably owing to receptor desensitization (21)(22)(23). Thus, kisspeptin may participate in GnRH pulse generation, although the underlying mechanisms remain elusive (24,25).…”
mentioning
confidence: 99%
“…In another study in prepubertal female monkeys, GnRH was suppressed for 90 minutes by peptide 234 suggesting that there is a lower KP tone 119 . Peptide 234 was also effective in suppressing LH (GnRH) pulsatility in ovariectomised ewes without affecting basal LH 109 and decreased LH pulse frequency, but not basal LH, when administered intra ARC in ovariectomised female rats 120 .…”
Section: Interrogating Kps Role In Physiology Using Antagonistsmentioning
confidence: 99%
“…In these treatments steroid hormones are lowered to castrate levels resulting in side effects such as hot flushes, reduced lean body mass, loss of libido and bone loss. The demonstration that KP antagonists reduce LH pulsatility 109,120 and inhibit the ovulatory LH surge 116 , but do not appear to affect basal LH, suggests that they may find clinical utility in conditions where maximal suppression of sex steroids is contra-indicated. Examples are benign prostatic hyperplasia, endometriosis and uterine fibroids where lowering of gonadal steroids could improve the conditions without the side effects of reducing steroid hormones to castrate levels.…”
Section: Potential Therapeutic Applications Of Kp Analoguesmentioning
confidence: 99%